Sodium chloride 0.9% versus Lactated Ringer in the management of severely dehydrated patients with choleriform diarrhoea - Cieza, Javier Antonio; Hinostroza, Juana; Huapaya, Julio Arturo; León, Cristian Paul (The Journal of Infection in Developing Countries, 2013)
Introduction: Although experience within Peru suggests clinical and physiological benefits of treating dehydration caused by diarrhoea with Lactated Ringer’s solution (LR) over sodium chloride 0.9%, (NaCl) there is little documented scientific evidence supporting this view. It is important to clarify this issue and determine the best solution for use during epidemics. Methodology: Forty patients suffering from dehydration due to choleriform diarrhoea were enrolled in the study. Twenty patients were treated using NaCl (Group A) and the other twenty with LR (Group B). After diuresis recovery was achieved, the patients were continued on a course of oral rehydration salts. Serum electrolytes, arterial pH, HCO3-, and pCO2 were measured at three stages: at admission, after diuresis recovery, and after 12 hours. Results: Acidosis was corrected more quickly with LR that NaCl. The hyperosmolality and hypernatremic states were corrected with both solutions. Conclusion: LR use resulted in a better clinical response than NaCl, illustrated by more rapid physiological correction, showing that mixed metabolic acidosis was corrected more quickly and more appropriately with this treatment.